2017
DOI: 10.3892/mmr.2017.8167
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of microRNA‑223‑3p in the tumorigenesis of hepatocellular carcinoma: A comprehensive study based on data mining and bioinformatics

Abstract: The aims of the present study were to examine the potential role of microRNA-233-3p (miR)-223-3p in the tumorigenesis of hepatocellular carcinoma (HCC), and to investigate its diagnostic accuracy and potential molecular mechanisms. The expression data of miR-223-3p in HCC were obtained from the Gene Expression Omnibus (GEO). Data for the precursor miR-223 were obtained from The Cancer Genome Atlas (TCGA). The diagnostic role of miR-223-3p was identified by the receiver operating curve (ROC), and the diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
0
6
0
1
Order By: Relevance
“…Evidence suggests that miR-223 expression and maturation are involved in the regulation of cell proliferation, hematopoietic development, and differentiation. 24 Dysregulated miR-223 expression has been implicated in a wide range of cancer subtypes, including oesophageal, gastric, colorectal, and ovarian cancer, together with leukemia, 25 and may be a useful biomarker for NSCLC 26 and HCC, 27 suggesting its complex role in cancer. Other studies have shown that miR-223 plays an important role in the metastasis of cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that miR-223 expression and maturation are involved in the regulation of cell proliferation, hematopoietic development, and differentiation. 24 Dysregulated miR-223 expression has been implicated in a wide range of cancer subtypes, including oesophageal, gastric, colorectal, and ovarian cancer, together with leukemia, 25 and may be a useful biomarker for NSCLC 26 and HCC, 27 suggesting its complex role in cancer. Other studies have shown that miR-223 plays an important role in the metastasis of cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Functional roles of the HCCseek-8 microRNAs in the progression of HCC have been previously documented [15][16][17][18][19][20][21][22][23][24]. The miR-145-5p [15], miR-148a-3p [16], miR-150-5p [17], miR-223-3p [19], and miR-424-5p [22] were found to be down-regulated in HCC.…”
Section: Discussionmentioning
confidence: 80%
“…Although some microRNAs in the HCCseek-8 panel have been linked to HCC detection and survival [5,7,18,23,24], analyzing multi-dimensional data could improve the prediction model [10][11][12]. In this study, we integrated multi-dimensional data such as the microRNA expressions, dynamic change of miRNA levels before and after surgery, and the traditional serum biomarkers for the prognosis of early HCC patients undergoing hepatectomy (Supplementary Figure 18).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no direct interaction of miRNA-223-3p with glycosylation pathways, it has been proven to target protein expression levels in pregnancy [45] and cancer [46]. In pregnancy, miRNA-223-3p regulates endometrial receptivity to blastocyst implantation by targeting leukemia inhibitory factor (LIF), which modulates biological processes such as decidualisation, embryo-endometrial interaction, blastocyst growth, trophoblast invasion and immune modulation [45].…”
Section: Exosomal Hsa-mir-223-3pmentioning
confidence: 99%